2010
DOI: 10.1214/09-aop513
|View full text |Cite
|
Sign up to set email alerts
|

On ergodicity of some Markov processes

Abstract: We formulate a criterion for the existence and uniqueness of an invariant measure for a Markov process taking values in a Polish phase space. In addition, weak-$^*$ ergodicity, that is, the weak convergence of the ergodic averages of the laws of the process starting from any initial distribution, is established. The principal assumptions are the existence of a lower bound for the ergodic averages of the transition probability function and its local uniform continuity. The latter is called the e-property. The g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 30 publications
2
112
0
Order By: Relevance
“…Next they also extended the technique to Markov operators acting on arbitrary Borel measures what allowed them to study operators appearing in the theory of fractal and semi-fractal sets [25]. Recently it was shown that the technique may be used in verifying the ergodic properties of solutions of infinitely dimensional stochastic differential equations [21]. In this paper we study Markov operators corresponding to iterated function systems with some disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Next they also extended the technique to Markov operators acting on arbitrary Borel measures what allowed them to study operators appearing in the theory of fractal and semi-fractal sets [25]. Recently it was shown that the technique may be used in verifying the ergodic properties of solutions of infinitely dimensional stochastic differential equations [21]. In this paper we study Markov operators corresponding to iterated function systems with some disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Let u(·, x) be the solution of (1) and v(·, x) be that of (31) with Z replaced by the stochastic convolution S. Since, by Remark 2.3, the embedding H ⊂ H is dense, one can findā ∈ H such that |ā − a| < ε 3 . Next, from Lemma 4.10 we infer the existence of a control c ∈ L 4 (0, T ; H ) ∩ C([0, T ]; H) such that and u c (T, x) =ā where u c (·, x) is defined by (33). Thus, using the decomposition u(·, x) = v(·, x) + S and the definition of u c (·, x) we infer that…”
Section: Lemma 410 For Any X X Fmentioning
confidence: 99%
“…However, several results about the qualitative or long-time behavior of solution of SPDEs driven by Lévy noise have been obtained during the last decade. We refer, among others, to [18,19,33,38,43,45,46,48,49] for results related to the ergodicity, irreducibility and mixing property of several classes of stochastic evolution equations driven by Lévy processes.…”
Section: Introductionmentioning
confidence: 99%
“…Remark One can show (see [7]) that to obtain the e-property in the case when X is a Hilbert space, it is enough to verify the above condition for every function with bounded Fréchet derivative. Definition 2.2 A semigroup (P t ) t≥0 is called averagely bounded if for any ε > 0 and bounded set A ⊂ X there is a bounded Borel set B ⊂ X such that lim sup…”
Section: Criterion On Stabilitymentioning
confidence: 99%